Study of the influence of wire metals on dissimilar welds. Issue 1 (1st March 2022) - Benlamnouar, M.F.; Bensaid, N.; Badji, R.; Saadi, T.; IDDIR, M.; Zidani, M.; SOUALILI, M.A.
Abstract: The aim of this study is to investigate the effect wire metal on microstructure and mechanical properties of dissimilar welds between HSLA-X70 high strength steel alloy and 304L austenitic stainless steel produced by automatic tungsten arc welding (TIG). The weld joints were prepared using E304L, E316L, E2209L, and E7010 wire metal. The mechanical characteristics obtained from hardness, tensile and impact testing, were correlated to the optical and SEM microscopy, to establish a relationship between wire metal composition and the microstructures in different weld regions. It is concluded that E2209 wire metal lead to improve in the resilience characteristics and tenacity with a slight reduction in the ultimate tensile strength and hardness.